Kontekstualisasi Konsep Jihad Dalam Al-Qur’an (Q.S Al-Nisa [4]: 95) Sebagai Upaya Preventif Covid-19) - Anam, Haikal Fadhil; Rofiq, Abdullah Khairur; Handary, Alvyta Nur; Lismawati, Lismawati (Universitas Islam Negeri Imam Bonjol Padang, 2020)
The concept of jihad from time to time and from generation to generation undergoes various changes depending on circumstances. However, most people only understand jihad as a battle on the battlefield with a sword or other weapon. Jihad is basically meant to exert power seriously. In the current context, in the midst of a global pandemic can resistance to the corona virus be considered a jihad? This is interesting and has novelty to study. This research is a library research (literature study). Research data sources consist of primary and secondary sources; the primary sourcis the Qur'an especially Q.S Al-Nisa [4]: 95 and secondary sources are all literature relating to the theme. The method used is descriptive-analytical method with Abdullah Saeed's contextual interpretation theory approach. Based on the results of research, resistance to the corona virus can be considered as jihad on the grounds that in the context of the first community jihad (in Q.S al-Nisa [4]: 9) was waging war to protect themselves, lives, property and others. If drawn into the context of the current pandemic, it has something in common, namely to protect lives. The difference lies in that if at that time the war against humans, while currently fighting against the virus. In relation to the intensity of the danger, it is now more dangerous because of its impacts on various things such as economic and social. If the form of jihad in the time of the Prophet was with war using weapons; swords, arrows, horses, spears, treasures and so on, so now the use of weapons; masks, soap, handsanitzer, tools of self protection, other medical devices, possessions and so on.